Role of RyR2 and SERCA2a in the Cardioprotective Effects of Vincanine and Pyrazoline Alkaloids - Zhumaev, Inoyat Zulfiqorovich; Ugli Boboev, Sadriddin Nurillo; Usmanov, Pulat Bekmuratovich; Rustamov, Shavkat Yusubovich; Zaripov, Abdisalim Abdikarimovich; Qurbonova, Shakhnoza Bakhtiyorovna; Mirzaeva, Yulduzkhon Takhirjanovna; Ugli Ibragimov, Eldor Bakhtiyor; Esimbetov, Adilbay Tlepovich; Adizov, Shahobiddin Mukhammadovich (Trends in Sciences, 2024)
In the conducted studies, the effect of vincanine and pyrazoline indole alkaloids on cardiac muscle cell sarcoplasmic reticulum (SR) Ca2+-transport systems (RyR2 and SERCA2a) was investigated under normal and hypoxic conditions. The effect of vincanine and pyrazoline on ryanodine receptor (RyR2) was evaluated in the presence of ruthenium red and it was found that the role of RyR2 in the positive inotropic effect of these alkaloids is small. Also, in the presence of cyclopiazonic acid (IC50 = 5.6 µM), an inhibitor of sarcoplasmic reticulum Ca2+-ATPase (SERCA2a), the positive inotropic effect of vincanine and pyrazoline alkaloids was reduced. In general, the positive inotropic effects and cardioprotective properties of vincanine and pyrazoline alkaloids are mediated by modulation of SERCA2a function. HIGHLIGHTS Vincanine and pyrazoline indole alkaloids have a positive inotropic effect on the force of papillary muscle contraction of the rat heart. Vincanine and pyrazoline indole alkaloids have a cardioprotective effect and effectively eliminate the disturbances in the papillary muscle contractile activity of the rat heart caused by hypoxia. Vincanine and pyrazoline alkaloids effectively reverse hypoxia-induced SERCA2a dysfunction and normalize changes in rat cardiac papillary muscle contractile activity. GRAPHICAL ABSTRACT